Analysis of the Relationship Between Contributing Factors and Body Image Among Medical Students - Abdullah, Ismiaty; Kadir, Sunarto; Karim, Cecy Rahma; Solang, Margaretha; Pateda, Sri Manovita (Universitas Negeri Gorontalo, 2025)
Introduction: Body image refers to an individual’s perception and evaluation of their physical appearance. A positive body image plays a crucial role in enhancing self-esteem, psychological resilience, and overall mental and physical well-being. In contrast, a negative body image has been linked to mental health problems, such as depression and disordered eating. This study aimed to examine the associations between various contributing factors and body image among medical students.Method: A quantitative cross-sectional study was conducted involving 67 medical students, selected through total population sampling. Data collection instruments included the Figure Rating Scale, Global Physical Activity Questionnaire (GPAQ), Dutch Eating Behavior Questionnaire (DEBQ), a 24-hour dietary recall, the Perceived Stress Scale (PSS-10), and the Rosenberg Self-Esteem Scale (RSES) to assess self-confidence. All instruments exhibited acceptable levels of validity and reliability. Data were analyzed using Chi-Square and Binary Logistic Regression Methods.Results: Significant associations were identified between body image and physical activity (p = 0.040), self-confidence (p = 0.018), and body mass index (BMI) (p = 0.001). Logistic regression analysis revealed that BMI (OR = 1.766, p = 0.002, 95% CI [0.644–2.888]), self-confidence (OR = 0.311, p = 0.045, 95% CI [0.099–0.975]), and physical activity (OR = 1.966, p = 0.031, 95% CI [1.063–3.831]) were significant predictors of body image.Conclusion: Body mass index, self-confidence, and physical activity were significantly associated with body image. The implementation of educational and psychological support programs is recommended to promote healthy self-perception and behavioral patterns among medical students.Keywords: Body image, body mass index, medical, motor activity, self-concept, students